Paisagem, amor e morte em O Largo da Palma, de Adonias Filho - Souza, Vanderlândia Lima de (2016)
The present work has been developed by the means of readings and analysis of theoretical and literary texts that articulate among each other promoting the discussion of elements like landscape, love and death represented in O Largo da Palma (2013), by Adonias Filho. Initially it will be presented a short summary of the author‘s works that focus the tragic in their character‘s lives. They are, Memórias de Lázaro (1961), Luanda, Beira, Bahia (1979), O Forte (1965) and As velhas (1982). The second part analyzes some thematic assumptions referring to landscape; the space and allegory, verifying how all the narratives develop in the allegoric space that expresses more than a simple metaphor. Next it highlights some reflections about the fusional love, the companionship and the loneliness, specifically in A moça dos pãezinhos de queijo, O largo de branco e A pedra. Posteriorly it presents considerations about death in the narratives Um corpo sem nome, Um avô muito velho e Os enforcados. It will be observing how the characters behave in face of love and death, as well as how the experience of life favors the passage to resumption and maturation in the person‘s wandering. It highlights yet the how the literature establishes a dialogue with historic factor and its relation with the fictional memory. The thematic cuttings highlighted were reasoned in the light of authors like Sergio Alves Peixto, Mirélia Ramos Basto Marcelino, Vânia Lúcia Menezes Torga, Maria Fernanda Arcanjo de Almeida e Benedito José de Araújo Veiga, Leandro Konder, André Comte-Sponvile, Flávio Gikovate, Maria Júlia kovács, Joel Candau, Friedrich Wilhelm Nietzsche, Juan-David Nasio, among others.